Improving Logistics Costs For Transportation And Trade Facilitation - Gonzalez, Julio A. (The World Bank, 2008)
Access to basic infrastructure services - roads, electricity, water, sanitation - and the efficient provision of the services, is a key challenge in the fight against poverty. Many of the poor (and particularly the extreme poor) in rural communities in Latin America live on average 5 kilometers or more from the nearest paved road, which is almost twice as far as non-poor rural households. There have been major improvements in access to water, sanitation, electricity, telecommunications, ports, and airports, but road coverage has not changed much, although some effort and resources have been invested to improve the quality of road networks. This paper focuses on the main determinants of logistics costs and physical access to services and, whenever possible, provides evidence of the effects of these determinants on competitiveness, growth, and poverty in Latin American economies. The analysis shows the impact of improving infrastructure and logistics costs on three fronts - macro (growth), micro (productivity at the firm level), and poverty (the earnings of poor/rural people). In addition, the paper provides recommendations and solutions that encompass a series of policies to reduce the prevalent high logistics costs and limited access to services in Latin America. The recommendations rely on applied economic analysis on logistics and trade facilitation